A σ(32) mutant with a single amino acid change in the highly conserved region 2.2 exhibits reduced core RNA polymerase affinity - Joo, Daniel M. (The National Academy of Sciences of the USA, 1997)
σ(32), the product of the rpoH gene in Escherichia coli, provides promoter specificity by interacting with core RNAP. Amino acid sequence alignment of σ(32) with other sigma factors in the σ(70) family has revealed regions of sequence homology. We have investigated the function of the most highly conserved region, 2.2, using purified products of various rpoH alleles. Core RNAP binding analysis by glycerol gradient sedimentation has revealed reduced core RNAP affinity for one of the mutant σ(32) proteins, Q80R. This reduced core interaction is exacerbated in the presence of σ(70), which competes with σ(32) for binding of core RNAP. When a different but more conserved amino acid was introduced at this position by site-directed mutagenesis (Q80N), this mutant sigma factor still displayed a significant reduction in its core RNAP affinity. Based on these results, we conclude that at least one specific amino acid in region 2.2 is involved in core RNAP interaction.